Anti-stress effects of ONO-2952, a novel translocator protein 18 kDa antagonist, in rats. (December 2015) - Mitsui, Katsukuni; Niwa, Tomohiro; Kawahara, Yuji; Morimoto, Noriko; Ohmoto, Kazuyuki; Kato, Masashi; Yamaura, Yoshiyuki; Yoshimoto, Naoki; Suna, Hideaki; Katsumata, Seishi
Abstract: Accumulating evidence has shown the pathophysiological significance of the translocator protein 18 kDa (TSPO) in the central nervous system. In this study, we evaluated the beneficial effects of ONO-2952, a novel TSPO antagonist in rat stress models. ONO-2952 potently bound both rat and human TSPO (Ki = 0.330–9.30 nmol/L) with high selectivity over other receptors, transporters, ion channels and enzymes. ONO-2952 inhibited both neurosteroid accumulation and noradrenaline release in the brain of rats exposed to acute stress. The inhibitory effect of ONO-2952 on stress-induced noradrenaline release was attenuated by co-treatment with the TSPO agonist CB34 in a dose-dependent manner. ONO-2952, at 0.3 mg/kg or higher, dose-dependently suppressed restraint stress-induced defecation in rats with brain TSPO occupancy of more than 50%. In addition, ONO-2952, at 1 mg/kg or higher, suppressed conditioned fear stress-induced freezing behavior in rats with an efficacy equivalent to that of diazepam, given orally at 3 mg/kg. Results of the passive avoidance learning test revealed that ONO-2952, unlike diazepam, did not affect learning and memory even at doses 10 times higher than its effective doses in the stress models. The present findings indicate that ONO-2952 is a promising candidate for the treatment of stress-related disorders. Highlights: ONO-2952 is a novel and orally-available TSPO antagonist with anti-stress effects. ONO-2952 inhibits noradrenaline release in the brain of rats exposed to stress. Beneficial effects of ONO-2952 correlate with this compound brain TSPO occupancy. ONO-2952, unlike diazepam, does not affect passive avoidance behavior. ONO-2952 is a promising candidate for the treatment of stress-related disorders.